Pengembangan Budaya Mutu Sekolah: Studi Kasus di SMP Negeri 1 Wirosari - Hana Tristiandari; Rina Nurhayati; Titik Haryati (IQRO: Journal of Islamic Education, 2024)
This study aims to describe the development of a quality culture at SMP Negeri 1 Wirosari as a case study. The research uses a qualitative approach with data collection through observation, interviews, and documentation. The results show that the school has succeeded in building a quality culture through strengthening vision and mission, adaptive and collaborative leadership, teacher competency development, active stakeholder involvement, and continuous evaluation. The implementation of a quality culture has a positive impact on academic and non-academic student achievement, teacher professionalism, management efficiency, and stakeholder satisfaction. However, challenges such as resistance to change, traditional mindset, and limited resources remain obstacles. The conclusion emphasizes the importance of leadership commitment, stakeholder participation, teacher competency development, and continuous evaluation in strengthening a sustainable quality culture.